(untitled) (Journal of Hama University, 2025)
This research aims to evaluate the availability of requirements for implementing work teams in the General Authority for Scientific Agricultural Research, and then present a set of proposals for the management of these institutions in a way that improves their level of performance. The researcher relied on the deductive approach as a general approach to thinking, where the researcher moved from the general to developing a set of hypotheses. He collected primary data through a questionnaire as a tool for the study, which was organized by referring to sources, periodicals, and articles that dealt with the axes and topics of the research. The questionnaire was distributed to a sample of Employees at Al-Hanadi station in Latakia. The researcher relied on the statistical analysis method, where the researcher transcribed the questionnaire into a regular database that was analyzed using the SPSS program (version no. 20), and the researcher used appropriate statistical tests to test the hypotheses: calculating the Cronbach’s alpha coefficient to measure the stability of the scale. One-sample T-test to test hypotheses. The most important results of the research were that there is no use and application of the concept of work teams in the institution under study, as it was found that there is a decline in the level of interaction, open communication, and effective leadership in the institution under study.